Evaluasi Pengelolaan Sumber Daya Manusia menggunakan Kerangka Kerja COBIT 5 (Studi Kasus : Dinas Komunikasi dan Informatika Kabupaten Sidoarjo) - Rifdah Nur Fadhilah; Widhy Hayuhardhika Nugraha Putra; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika Kabupaten Sidoarjo provides services to the public in the field of information and communication, statistics and coding transparently and accountably in the field of communication and informatics. To provide maximum service, Dinas Komunikasi dan Informatika Kabupaten Sidoarjo must have sufficient and qualified human resources. Based on the results of the interview, several problems were found in managing human resources. To find out the current conditions in human resource management can be done Capability level assessment in the EDM04 process Ensure Resource Optimization and APO07 Manage Human Resources by using the COBIT 5 framework. Data collection is done through interviews, observations, and assessment sheets. Assessment is done in stages from level 0 Incomplete Process to level 5 Optimization Process to find out the value of capability level. Then, do an analysis of the value of the capability level obtained and the level target. Then, improvements will be obtained to improve human resources in the organization. Capability level for EDM04 Ensure Resource Optimization is at level 1 with level target at level 2 and for APO07 Manage Human Resources is at level 2 with level target at level 3. Thus, the gaps obtained by each process are as many as 1. Recommendations for improvement given refer to the activities and documents related to each process.